Modern Weapons and Military Equipment for Issue 1/2015 - Tišma, Mladen R. (Vojnotehnički glasnik / Military Technical Courier, 2014)
Contract to equip Eurofighter with AESA radar Kaptor E signed; Carrier-based version of PAK-FA multirole fighter in plan; Flying car from Slovakia; F-35C first carrier landing; Chinese J-31 fighter aircraft officially presented to the public; Embraer unveiled a prototype of KC-390 transport aircraft; Russia develops new AWACS under the designation A-100; The first modernized bomber Tu-160 flies; Iran conducted a successful test flight of unmanned aircraft reverse-engineered from American RQ-170; China and Russia jointly to develop the largest and most powerful helicopter in the world; Lithuanians develops new VHF early warning radar; Ukraine considers the licensed production of L-15 aircraft; The new missile to equip the aircraft PAK-FA entered serial production in 2015; USN to convert TV-guided Mavericks to laser guided missiles; Lockheed Martin to equip F-22 fighters with AIM-9X missiles; China launched new military satellites; Ukraine is developing new missiles and trackers; Russia is developing a new generation of satellites for early warning.